The use of Immunoglobulin Therapy in Primary Immunodeficiency Diseases - Azizi, Gholamreza; Abolhassani, Hassan; Hosein Asgardoon, Mohammad; Rahnavard, Javad; Zaki dizaji, Majid; Yazdani, Reza; Mohammadi, Javad; Aghamohammadi, Asghar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2016)
Immunoglobulin therapy represents a lifesaving intervention for many patients with primary immunodeficiency (PID). Antibody defects represent approximately half of the well-known PIDs requiring immunoglobulin replacement therapy. Following immunoglobulin therapy in PID patients, protection against serious upper and lower respiratory tract infections and pulmonary function improves which leads to an increase in the quality of life of these patients. Successful treatment of PID patients depends on the type of immunodeficiency, regular monitoring of the patient, comorbidities of the patient, and the availability of the products.
Keywords: primary immunodeficiency diseases